2018
DOI: 10.1108/ijlm-04-2017-0093
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain resilience: a dynamic and multidimensional approach

Abstract: Purpose The purpose of this paper is to present a conceptual framework on resilience types in supply chain networks. Design/methodology/approach Using a complex adaptive systems perspective as an organizing framework, the paper explores three forms of resilience: engineering, ecological and evolutionary and their antecedents and links these to four phases of supply chain resilience (SCRES): readiness, response, recovery, growth and renewal. Findings Resilient supply chains need all three forms of resilienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
192
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(217 citation statements)
references
References 74 publications
(122 reference statements)
2
192
0
Order By: Relevance
“…Srinivasan and Swink (2018) argue that organizational flexibility in terms of supply chain is defined as the ability of the supply chain managers to reconfigure their internal supply chains quickly and efficiently to adapt to the changing demand and supply market conditions. Adobor and McMullen (2018) argue that disruptions to supply chains can have significant economic impacts. Hence, managing risk and vulnerability associated with supply chains have attracted increasing attentions from practitioners and policy makers.…”
Section: Organizational Flexibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Srinivasan and Swink (2018) argue that organizational flexibility in terms of supply chain is defined as the ability of the supply chain managers to reconfigure their internal supply chains quickly and efficiently to adapt to the changing demand and supply market conditions. Adobor and McMullen (2018) argue that disruptions to supply chains can have significant economic impacts. Hence, managing risk and vulnerability associated with supply chains have attracted increasing attentions from practitioners and policy makers.…”
Section: Organizational Flexibilitymentioning
confidence: 99%
“…Hence, managing risk and vulnerability associated with supply chains have attracted increasing attentions from practitioners and policy makers. Holling (1973) argue that resilience, the capacity of a system to adapt to change and deal with surprise while retaining the system's basic function and structure, has evolved as an important aspect for managing supply chain risk and vulnerability (Ponomarov and Holcomb, 2009;Pettit et al, 2010;Adobor and McMullen, 2018).The resilience is a multidisciplinary concept (Chowdhury and Quaddus, 2017). Ates and Bititci (2011) argue that resilience in organizational context as an organizational capability to survive in turbulent environment.…”
Section: Organizational Flexibilitymentioning
confidence: 99%
“…Accordingly, it has been suggested that learning and growth represent a fourth phase of resilience after the recovery stage (e.g., Adobor and McMullen, 2018;Hohenstein et al, 2015) via learning from experiences (Pettit et al, 2010) or training and development (Blackhurst et al, 2011;Ritchie and Brindley, 2007). Yet, despite this acknowledgement of p p l y C h a i n M a n a g e m e n t : a n I n t e r n a t i o n a l J o u r n a l 5 the role of learning for SCRes (Chowdhury and Quaddas, 2016), how organisations can learn and adapt their routines to foster SCRes has not been explicitly theorised.…”
Section: Supply Chain Resiliencementioning
confidence: 99%
“…Using safety stock to maintain the capacity to respond to any disruption in the supply chain Rice Jr. and Caniato (2003); Sheffi and Rice Jr. (2005); Soni et al (2015); Ali et al (2017); Adobor and McMullen (2018)…”
Section: Redundancymentioning
confidence: 99%